Application of 3D Simulation Software in Chemotherapy and Hepatoblastoma Surgery in Children - Liu, Jie; Xiu, Wenli; Duan, Guangqi; Dong, Qian (Frontiers in Surgery, 2022)
Purpose: To explore the clinical value of a computer-assisted surgery system (Hisense CAS) in hepatoblastoma (HB) surgery in children after neoadjuvant chemotherapy. Patients and Methods: The clinical medical records of children with HB treated after neoadjuvant chemotherapy at the Affiliated Hospital of Qingdao University from January 2016 to January 2019 were analyzed retrospectively. Results: A total of 21 children were enrolled in this study, including 13 boys and 8 girls. All cases successfully underwent three-dimensional (3D) reconstruction of the liver and tumor using Hisense CAS, simulated hepatectomy, and hepatectomy according to the preoperative operation plan. There were 12 cases of right hemihepatectomy, four cases of right trefoil hepatectomy, one case of left lobe hepatectomy, three cases of middle lobe hepatectomy, and one case of V and VI segment hepatectomy. All children recovered well after the operation. The follow-up ranged from 5 months to 3 years. One child died of systemic metastasis 8 months after the operation. One child received one course of chemotherapy after the operation. Due to the serious reaction to the chemotherapy, the family refused further treatment and follow-up. The remaining 19 children had no complications or recurrence. Conclusion: The Hisense CAS can clearly and intuitively display the position and shape of the HB before and after chemotherapy and its relationship with the intrahepatic pipeline system and accurately evaluate the changes in tumor volume and the distance between important blood vessels, which is conducive to the operator selecting the best operation opportunity, timely formulating the best operation plan and implementing individualized and accurate liver tumor resection.